New insights into the antibacterial mode of action of quercetin against uropathogen Serratia marcescens in-vivo and in-vitro - Suganya Kannan; Jeyakumar Balakrishnan; Ambujam Govindasamy; R. Arunagiri (Scientific Reports, 2022)
Abstract In the course of a quest for therapeutic agents inhibiting uropathogens, the rise and universal blowout of antibiotic-resistant organisms is a wide problem. To overcome this matter, exploration of alternative antimicrobials is necessary. The antimicrobial potential of quercetin has been widely described against some pathogenic microorganisms, but to the best of our knowledge, no report exists against the pathogenicity of uropathogenic Serratia marcescens. Hence, the present study focused on the antibacterial mechanism of action of quercetin, a flavonoid against the uropathogen Serratia marcescens. Quercetin was evaluated for its anti-QS activity, and the attained outcomes showed that quercetin inhibited QS-mediated virulence factors such as biofilm formation, exopolysaccharides, swarming motility and prodigiosin in Serratia marcescens. The proposed mechanism of action of quercetin greatly influences cell metabolism and extracellular polysaccharide synthesis and damages the cell membrane, as revealed through global metabolome profiling. In vivo experiments revealed that treatment with quercetin prolonged the life expectancy of infected Caenorhabditis elegans and reduced the colonization of Serratia marcescens. Hence, the current study reveals the use of quercetin as a probable substitute for traditional antibiotics in the treatment of uropathogen infections driven by biofilms.